Recent progress in tissue enhanced spectroscopy for cancer detection - Tuchin, Valery V (2022)
Spectroscopy methods can be used for pathology identification and monitoring, but their applications are limited by light scattering if the disease is located in deeper tissue layers. The first study presented in this paper shows that the simple application of spectroscopy measurements allows colorectal cancer discrimination through the identification of different pigment content in normal and diseased tissues. The other two studies demonstrate that by combining sensitive spectroscopy measurements in a wide spectral range with optical clearing (OC) treatments is also useful for cancer discrimination. In the second study, by using spectral collimated transmittance (Tc) measurements during OC treatments, it was possible to estimate the diffusion coefficient of glucose in normal and pathological colorectal mucosa as: Dglucose = 5.8×10-7 cm2/s and Dglucose = 4.4×10-7 cm2/s, respectively. An additional result of this study shows that the mobile water content is about 5% higher in pathological mucosa. In the third study, by analyzing the OC efficiency in the deep UV range, it was possible to obtain different protein dissociation rates in normal (27.4) and pathological (79.1) mucosa tissues at 93%-glycerol treatment. Such methods can be applied to study other types of cancer or other diseases, and their conversion into noninvasive procedures, based on diffuse reflectance spectroscopy, is to be expected. © Anita Publications. All rights reserved.